13C NMR isotopomeric analysis and its application in the study of endocrine cell metabolism and function - Simpson, Nicholas E.; Constantini, Ioannis (Acta Biomedica Atenei Parmensis, 2007)
Defining mechanisms and enzymatic paths critical to cellular function (e.g., secretion) of endocrine cells is a key research goal that can lead toward novel avenues of therapeutic intervention for a variety of disorders. 13C NMR spectroscopy and isotopomer analysis of cell extracts are excellent tools to quantitatively assess metabolism through intermediate labeling and estimate carbon entry to the TCA cycle. Discussed are: cell lines and in vitro culturing; extraction of intracellular material; NMR spectroscopy of the extract; isotopomeric analysis and modeling to obtain relative metabolic fluxes to the TCA cycle. This paper describes issues related to the application of NMR spectroscopic techniques on cell line extracts. Included are results of two studies that illustrate considerations that must be taken when performing analogous studies on neuroendocrine tissue: one involving the effect of media composition on cell behavior and isotopomer labeling; the second looking at effects of applying different metabolic models to 13C data and inferences that may be drawn. NMR isotopomeric analysis is a powerful technique that may be applied to better understand endocrine cell function.